Dietary supplements compendium. (United States Pharmacopeial Convention, 2015)
The 2015 USP Dietary Supplements Compendium (DSC) has been significantly updated and expanded into a two-volume set. The new DSC features are 75 new dietary supplement monographs--nearly 500 in all--from USP 38-NF 33 through the First Supplement; 27 new General Chapters; More than 175 excipient monographs; Over 200 Food Chemicals Codex (FCC) monographs; More than 40 new and revised DSC admission evaluations and Includes over 150 added pages of color plates and illustrations.
Includes index.
Keywords: Dietary supplements industry.; Dietary supplements.; elektronické knihy; electronic books